Clinical and experimental research of Nucleo CMF Forte efficiency in case of nerve injury - Фурман, Руслан Леонідович; Барило, Олександр Семенович; Король, Анатолій Петрович (ScienceRise: Medical Science, 2016)
The object of our research was: morphological ultrastructural changes in nerves after nerve injury experimental modeling; clinical signs of inferior alveolar nerve trauma in cases of mandible fractures. Materials and methods. Surgery with nerve mobilization, and nerve compression by Pean forceps for 5 minutes were carried out. Then, animal control, treatment using Nucleo CMF Forte within 10 days, and collection of material for histological study at the end of research were carried out. Clinical efficiency of Nucleo CMF Forte was studied. The study of subjective (spontaneous pain parameters, NTSS – 9 scale), objective (tactile sensitivity excitation degree, pain sensitivity excitation area, symptoms of thermal heat and cold hyperalgesia, dynamic and static components of mechanical hyperalgesia), and instrumental study (sensitivity threshold value, pain threshold, pain tolerance level) was carried out. Results. Ultrastructural research revealed significant degenerative and destructive changes in axial cylinders axoplasm after proximal section clamping, clamping place and distal section of sciatic nerve. Significant destructive changes were found in myelin sheath. Myelin sheath was homogeneous and structureless in some nerve fibers. In other nerve fibers, myelin sheath characterized by randomly oriented filamentary formations, which were divided by low electron density areas. After Nucleo CMF Forte treatment, both in proximal section, and in clamping place, and in distal section of sciatic nerve ultrastructural changes were less pronounced, comparing with rats, not being treated after sciatic nerve compression. Nerve roots swelling, as well as nerve fibers degeneration also were less pronounced. Along with single myelin fibers with destruction signs, fibers with minor changes were located, as well as similar ones in intact rats. In distal section of sciatic nerve ultrastructural signs were found, indicating the increased intracellular regeneration. Clinical research has shown following results. A spontaneous pain indicators 0.22±0.42 points, 6.72 times less than the comparison group (р<0.05). NTSS – 9 scale indicators were 2.,53±0.50 points, 5.77 times less than the comparison group (р<0.05). Tactile sensitivity excitation were 0.84±0.36 points, 3.2 times less than the comparison group (р<0.05). Pain sensitivity excitation area was 2.96±0.31 cm2, 2.63 times less than the same in the comparison group (р<0.05). Symptoms of thermal heat and cold hyperalgesia, dynamic and static components of mechanical hyperalgesia completely disappeared. Values of sensitivity threshold (16.73±0.75), pain threshold (37.46±0.79), and pain tolerance level (53.09±0.79) almost meet all indices of the undamaged side (15.68±1.41, 36.58±1.01, and 52.24±1.01, respectively) (р<0.05). The obtained results show a significant positive clinical efficiency of the remedy, containing nucleotides. Conclusion. Considering all mentioned ultrastructural morphological changes, we certainly can affirm, that the use of Nucleo CMF Forte affects favorably preservation and restoration of nerve structures, and promotes its quick and complete recovery after injury. The given remedy improves nerve fibers recovery both in proximal section, and in nerve fiber injury place (compression), and in distal section, showing itself as neuroprotective and neuroregenerative agent at the tissue and cellular levels. The mentioned diagnostic methods can detect the signs of inferior alveolar nerve dysfunction, as well as allow studying nerve recovery dynamics during the treatment. The obtained results of research point to clinical efficiency of the remedy, containing nucleotides